R.H. Clark, The Code of the State of Georgia (1882) , Part V, Title I, Division IX, § 4528 - (:unkn) unknown (General Publisher, 1882)
Prohibited carry of any dirk, Bowie knife, pistol, or revolver, or any kind of deadly weapon to any Court of justice, or any election ground or precinct, or any place of public worship, or any other public gathering in this State. Violators guilty of a misdemeanor, punished by fine not less than twenty nor more than fifty dollars, or imprisoned not less than ten nor more than twenty days, or both at discretion of the court.
--
Keywords: CARRY - CERTAIN PUBLIC PLACES